Laser-induced breakdown spectroscopy (LIBS) : fundamentals and applications - Miziolek, Andrzej W., 1950-; Palleschi, V.; Schechter, Israel (Cambridge University Press, 2006)
This is the first comprehensive reference explaining the fundamentals of the LIBS phenomenon, its history and its fascinating applications across eighteen chapters written by recognized leaders in the field. This book will be of significant interest to researchers in chemical and materials analysis within academia and industry.